Adult and offspring size in the ocean over 17 orders of magnitude follows two life history strategies. Issue 12 (1st December 2015) - Neuheimer, A. B.; Hartvig, M.; Heuschele, J.; Hylander, S.; Kiørboe, T.; Olsson, K. H.; Sainmont, J.; Andersen, K. H.
Abstract : Explaining variability in offspring vs. adult size among groups is a necessary step to determine the evolutionary and environmental constraints shaping variability in life history strategies. This is of particular interest for life in the ocean where a diversity of offspring development strategies is observed along with variability in physical and biological forcing factors in space and time. We compiled adult and offspring size for 407 pelagic marine species covering more than 17 orders of magnitude in body mass including Cephalopoda, Cnidaria, Crustaceans, Ctenophora, Elasmobranchii, Mammalia, Sagittoidea, and Teleost. We find marine life following one of two distinct strategies, with offspring size being either proportional to adult size (e.g., Crustaceans, Elasmobranchii, and Mammalia) or invariant with adult size (e.g., Cephalopoda, Cnidaria, Sagittoidea, Teleosts, and possibly Ctenophora). We discuss where these two strategies occur and how these patterns (along with the relative size of the offspring) may be shaped by physical and biological constraints in the organism's environment. This adaptive environment along with the evolutionary history of the different groups shape observed life history strategies and possible group‐specific responses to changing environmental conditions (e.g., production and distribution).